G-C3N4 loaded LiAlH4 composite material based on anti-solvent method, preparation method and application

LiAlH4 was loaded on g-C3N4 nanosheets by anti-solvent method, which solved the problem of slow hydrogen release rate and poor reversibility of LiAlH4 hydrogen storage material, achieved efficient nanoification and uniform loading, and improved hydrogen storage performance.

CN120440835APending Publication Date: 2025-08-08XIAN TECH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510355152.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-08-08

AI Technical Summary

Technical Problem

The existing LiAlH4 hydrogen storage materials have slow hydrogen release speed and poor reversibility, which limit their application in automotive hydrogen storage and other fields.

Method used

LiAlH4 was loaded on g-C3N4 nanosheets by anti-solvent method, and the burst nucleation process was initiated by the difference in solubility of diethyl ether and n-pentane to achieve nanoification and uniform loading of LiAlH4, and a g-C3N4/LiAlH4 composite material was prepared.

Benefits of technology

The hydrogen release rate and reversibility of LiAlH4 are significantly improved. The hydrogen release capacity is about 0.7 wt% before 150°C, and about 5.4 wt% hydrogen is released within a few seconds at 150°C, which reduces the dehydrogen activation energy and improves the thermodynamic and kinetic properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120440835A_ABST
    Figure CN120440835A_ABST
Patent Text Reader

Abstract

The invention discloses a g-C3N4 loaded LiAlH4 composite material based on an anti-solvent method as well as a preparation method and application of the g-C3N4 loaded LiAlH4 composite material. The composite material is named g-C3N4 / LiAlH4, the ratio of the g-C3N4 to the LiAlH4 is (1-5): (5-10), the macroscopic form of the composite material is a solid nano particle, and the particle size is 10-20 nm. The preparation method comprises the following steps: weighing LiAlH4 and anhydrous LiI, dissolving the LiAlH4 and the anhydrous LiI in diethyl ether, and filtering out insoluble substances to form a solution A; weighing g-C3N4, dissolving g-C3N4 in diethyl ether, and performing ultrasonic treatment to form a solution B; mixing the solution A with the solution B to form a solution C; cooling the n-pentane to-10 DEG C to 0 DEG C by using a semiconductor cooler; ultrasonic shearing dispersion is started, so that the n-pentane liquid level does not fluctuate; absorbing the solution C, and dropwise adding the solution C into n-pentane during the ultrasonic starting period to form a turbid liquid D; centrifuging or performing suction filtration on the turbid liquid D to obtain a precipitate; and carrying out vacuum drying on the precipitate to obtain the g-C3N4 / LiAlH4. According to the preparation method, LiAlH4 is loaded on g-C3N4 in a nanocrystallization manner by utilizing an anti-solvent method, the hydrogen storage performance of the composite material is remarkably improved, the process is simple, the thermodynamic and dynamic performance of LiAlH4 is optimized, and the preparation method has potential application value in the field of solid hydrogen storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy materials, and specifically relates to a g-C3N4 loaded LiAlH4 composite material based on an anti-solvent method, a preparation method and an application thereof. Background Art

[0002] In the field of new energy technologies, hydrogen is considered a crucial component of future energy due to its high energy density and zero-emission characteristics. However, the storage and transportation of hydrogen remain key challenges hindering its widespread application. Traditional liquid and gaseous hydrogen storage methods suffer from low safety and high energy consumption. Therefore, solid-state hydrogen storage technology has attracted widespread attention due to its high storage capacity and excellent safety.

[0003] LiAlH4, as a high-density solid-state hydrogen storage material, theoretically has a mass hydrogen storage density of up to 7.9 wt%, and its dehydrogenation temperature is relatively low, making it a highly promising candidate for hydrogen storage. However, in practical applications, LiAlH4 faces the challenges of slow hydrogen desorption and poor reversibility, limiting its application in areas such as on-board hydrogen storage. In the prior art, improving the hydrogen storage performance of LiAlH4 through nano-scaling and catalyst modification has been widely studied. For example, nano-scaling LiAlH4 through mechanical ball milling can improve its hydrogen desorption rate to a certain extent, but this method is complex and costly, and the nanoparticles easily agglomerate, making it difficult to achieve large-scale application. In addition, patent document (CN 118491553 A) discloses an N-rGO@NiCo / LiAlH4 composite material. NiCo catalyst is loaded on an N-rGO substrate through hydrothermal synthesis and impregnation, which reduces the initial hydrogen desorption temperature of LiAlH4 to 103°C and exhibits certain hydrogen desorption performance (e.g., 1.5 wt%) at low temperatures (e.g., 80°C). However, the preparation process of this method is complicated, and the hydrogen decomposition rate and high-temperature hydrogen decomposition efficiency still need to be further improved. The second-step hydrogen decomposition temperature of the material is relatively high, and the reversibility is still not ideal. Summary of the Invention

[0004] The present invention proposes a g-C3N4 loaded LiAlH4 composite material based on the anti-solvent method, a preparation method and an application thereof, aiming to solve the problems of slow hydrogen release rate and poor reversibility of LiAlH4 hydrogen storage materials in the prior art.

[0005] In order to achieve the above object, the technical solution of the present invention is as follows:

[0006] In the first aspect, the present invention provides a g-C3N4 loaded LiAlH4 composite material based on the anti-solvent method, characterized in that the composite material is named g-C3N4 / LiAlH4, the mass ratio range of each component is g-C3N4:LiAlH4=1-5:5-10, and the macroscopic morphology of the composite material is solid nanoparticles with a particle size of 10-20nm.

[0007] Furthermore, the mass ratio of each component is g-C3N4:LiAlH4=5:5.

[0008] In a second aspect, the present invention provides a method for preparing the composite material, comprising:

[0009] S1. Weigh LiAlH4 and anhydrous LiI and dissolve them in ether. Stir thoroughly and filter with a syringe filter to remove insoluble matter to form solution A.

[0010] S2. Weigh g-C3N4 and dissolve it in ether, then sonicate to form solution B.

[0011] S3, mixing solution A and solution B, and stirring thoroughly to form solution C;

[0012] S4. Add n-pentane into the stainless steel cup, with the ratio of n-pentane to solution C being 6-20:1, and cool the n-pentane to -10-0°C using a semiconductor refrigerator;

[0013] S5. Insert the ultrasonic shear disperser 1-2 cm below the n-pentane liquid surface, start ultrasonic shear dispersion, and adjust the power so that the n-pentane liquid surface does not fluctuate;

[0014] S6. Use a pipette to draw up solution C, and add it dropwise to n-pentane while ultrasound is on to form suspension D. During this process, keep the semiconductor cooler on.

[0015] S7, after the dropwise addition is completed, continue to perform ultrasonic shearing dispersion;

[0016] S8. Centrifuge or filter the suspension D to obtain a precipitate;

[0017] S9. The precipitate was transferred to a tube furnace and vacuum dried at 30-60°C for 12 hours to obtain a g-C3N4 loaded LiAlH4 composite material.

[0018] Furthermore, in S1, the molar ratio of LiAlH4 to anhydrous LiI is 10-30:1.

[0019] Furthermore, in S2, the ultrasonic treatment time is 0.5-3 hours.

[0020] Furthermore, in S5, the ultrasonic shearing dispersion procedure is ultrasonication for 5-20 seconds, and pause for 5-20 seconds, with a total duration of 10-30 minutes.

[0021] Furthermore, in S6, the dropping speed of solution C is 0.5-2 mL / min.

[0022] Furthermore, in S7, the duration of the ultrasonic shearing dispersion is 5-10 minutes.

[0023] Furthermore, in S8, the centrifugal speed is 5000-10000 rpm.

[0024] In a third aspect, the present invention provides applications of the composite material in the field of solid-state hydrogen storage.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] In the embodiment of the present invention, a g-C3N4-loaded LiAlH4 composite material is prepared by an anti-solvent method. LiAlH4 is loaded on g-C3N4 nanosheets in the form of nanoparticles, and the high specific surface area of g-C3N4 is utilized to improve the hydrogen storage performance of the material. Experimental data show that the composite material has a hydrogen release capacity of approximately 0.7 wt% before 150°C, and the hydrogen release rate is relatively slow. However, at approximately 150°C, the composite material can release approximately 5.4 wt% of hydrogen within a few seconds, which is an increase in the hydrogen release rate compared to the original LiAlH4. The dehydrogenation activation energy is reduced to 113.24 kJ·mol -1 and 104.223 kJ·mol -1 , compared with unmodified LiAlH4, the kinetics of the second step hydrogen release is improved.

[0027] The method of the present invention combines the anti-solvent method with the high specific surface area material g-C3N4 for the first time, and triggers the explosive nucleation process through the solubility difference between the good solvent (ether) and the poor solvent (n-pentane), thereby achieving the nano-sizing and uniform loading of LiAlH4; the innovation of this preparation method lies in its simple and efficient process, avoiding complex operations such as traditional mechanical ball milling, while significantly improving the thermodynamic and kinetic properties of the material; XRD and TEM analysis further confirmed that LiAlH4 nanoparticles grow on the surface of g-C3N4 and the lattice structure is optimized (such as the peak shift caused by LiI doping), providing a new thermodynamic modification path for improving the performance of hydrogen storage materials.

[0028] The g-C3N4 / LiAlH4 composite material, prepared by the antisolvent method, not only exhibits significant advantages in hydrogen storage capacity and dehydrogenation rate, but also demonstrates good structural stability and thermodynamic modification potential. DSC testing reveals a strong exothermic peak during the dehydrogenation process, demonstrating the profound thermodynamic impact of the antisolvent method combined with the g-C3N4 carrier. In situ XRD analysis further reveals the phase evolution of the material during rapid dehydrogenation, verifying its efficient dehydrogenation mechanism. This comprehensive performance improvement gives the composite material broad application prospects in the field of solid-state hydrogen storage, providing a practical solution for the safe and efficient storage and transportation of hydrogen energy.

[0029] Of course, the implementation of the various technical solutions of the present invention does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying any creative work, they can also obtain drawings of other embodiments based on these drawings.

[0031] Figure 1 This is the X-ray diffraction pattern of the g-C3N4 / LiAlH4 composite material obtained in Example 1;

[0032] Figure 2 SEM images of the g-C3N4 / LiAlH4 composite material prepared in Example 1 at different magnifications;

[0033] Figure 3 TEM image and element distribution analysis diagram of the g-C3N4 / LiAlH4 composite material prepared in Example 1;

[0034] Figure 4 This is a graph showing the non-isothermal hydrogen release performance of the g-C3N4 / LiAlH4 composite material obtained in Example 1;

[0035] Figure 5 Temperature change and hydrogen gas mass spectrometry of the g-C3N4 / LiAlH4 composite material prepared in Example 1 at heating rates of 3K / min, 5K / min, and 10K / min;

[0036] Figure 6 Linear fitting of the Kissinger equation for the g-C3N4 / LiAlH4 composite material obtained in Example 1;

[0037] Figure 7The mass spectrometry signal of the g-C3N4 / LiAlH4 composite material obtained in Example 1;

[0038] Figure 8 The differential thermal scanning signal of the g-C3N4 / LiAlH4 composite material obtained in Example 1;

[0039] Figure 9 This is the in-situ X-ray diffraction pattern of the g-C3N4 / LiAlH4 composite material obtained in Example 1 at 30°C-250°C. DETAILED DESCRIPTION

[0040] The present invention will be further described in detail below by means of specific embodiments in conjunction with the accompanying drawings. Similar elements in different embodiments are numbered with associated similar elements. In the following embodiments, many detailed descriptions are provided to enable the present application to be better understood. However, those skilled in the art will readily appreciate that some of the features may be omitted in different circumstances, or may be replaced by other elements, materials, or methods. In some cases, some operations related to the present application are not shown or described in the specification. This is to avoid the core portion of the present application being overwhelmed by excessive descriptions, and for those skilled in the art, it is not necessary to describe these related operations in detail. They will fully understand the related operations based on the description in the specification and the general technical knowledge in the art.

[0041] In addition, the features, operations, or characteristics described in the specification may be combined in any appropriate manner to form various embodiments. Furthermore, the steps or actions in the method description may be reordered or adjusted in a manner readily apparent to those skilled in the art. Therefore, the various sequences in the specification and drawings are provided solely for the purpose of clearly describing a particular embodiment and are not intended to be mandatory, unless otherwise specified.

[0042] This paper proposes a method for preparing LiAlH nanoparticles loaded on g-C3N4 nanosheets using an antisolvent method. Nanoparticles approximately 20 nm in size are successfully obtained, and the material achieves rapid hydrogen release within seconds. Below 150°C, the material releases hydrogen very slowly, with a capacity of approximately 0.7 wt%. However, at approximately 150°C, the release rate increases dramatically, releasing approximately 5.4 wt% of gas within a few seconds. This invention demonstrates significant advantages in both hydrogen storage capacity and efficiency, providing a new solution for the development of solid-state hydrogen storage technology.

[0043] Some of the terms involved in the present invention are explained as follows:

[0044] LiAlH4: lithium aluminum hydride;

[0045] g-C3N4: graphitic carbon nitride.

[0046] The present invention provides a g-C3N4 loaded LiAlH4 composite material based on an anti-solvent method, a preparation method and an application thereof. The preparation method of the composite material is summarized as follows:

[0047] LiAlH4 was loaded on g-C3N4 using the anti-solvent method. The resulting composite material was named g-C3N4 / LiAlH4. The mass ratio of the components ranged from g-C3N4:LiAlH4=1-5:5-10. The macroscopic morphology of the composite material was solid nanoparticles.

[0048] The resulting composite material exhibits the advantages of rapid hydrogen release and thermodynamic optimization, and can be widely used in solid-state hydrogen storage materials. Specifically, it can be used in scenarios such as on-board fuel cell hydrogen supply modules, portable power supply equipment, and buffer materials for stationary hydrogen storage stations.

[0049] The present invention will be further described below through several specific embodiments:

[0050] Example 1:

[0051] A method for preparing a g-C3N4-loaded LiAlH4 composite material based on an antisolvent method comprises the following steps:

[0052] S1. Weigh LiAlH4 and anhydrous LiI and dissolve them in ether, stir thoroughly and filter with a syringe filter to remove insoluble matter to form a solution A, wherein the molar ratio of LiAlH4 to anhydrous LiI is 20:1;

[0053] S2. Weigh g-C3N4 and dissolve it in ether. Ultrasonicate for 1 hour to form solution B.

[0054] S3. Mix solution A and solution B and stir thoroughly to form solution C;

[0055] S4. Add n-pentane to the stainless steel cup at a ratio of 15:1. Use a semiconductor cooler to cool the n-pentane to 0°C.

[0056] S5. Insert the ultrasonic shear disperser 1-2 cm below the n-pentane liquid level, start ultrasonic shear dispersion, adjust the power so that the n-pentane liquid level does not fluctuate, and perform ultrasonic shear dispersion for 15 seconds and 15 seconds, for a total of 10 minutes;

[0057] S6. Pipette solution C and add it dropwise to n-pentane while ultrasound is on to form suspension D. Keep the semiconductor cooler on during this process.

[0058] S7. After the addition is completed, continue ultrasonic shear dispersion for 5 minutes;

[0059] S8. The suspension D was centrifuged at 8000 rpm to obtain a precipitate;

[0060] S9. The precipitate was transferred to a tube furnace and dried in vacuum at 45 °C for 12 h to obtain a g-C3N4-loaded LiAlH4 composite material.

[0061] The mass ratio of the components of the composite material prepared in this example is g-C3N4:LiAlH4=5:5, and the macroscopic morphology of the composite material is solid nanoparticles.

[0062] In order to determine the phase structure of the composite material prepared in this example, the substances contained in the material were characterized by XRD, such as Figure 1 As shown, the most important peak in the material is the peak of LiAlH4 material, which corresponds to the standard PDF card (PDF#12-0473). In addition, the characteristic peaks of g-C3N4 material are well preserved, among which the peak at 12.1° corresponds to the (100) crystal plane of g-C3N4, and the peak at 27° corresponds to the (002) crystal plane of g-C3N4 and coincides with the diffraction peak of LiAlH4. In addition, the diffraction peak at 25.6° corresponding to the (111) crystal plane of LiI and the peak at 52.8° corresponding to the (111) diffraction peak of the material are also found. The diffraction peaks of the corresponding materials in the area with an angle greater than 50° are retrieved, which are mainly related to LiAl2H7 and LiAl4H 13 The results are consistent, a finding not previously reported in material synthesis. Furthermore, compared to standard PDF charts, some individual peaks in the material exhibit a shift toward higher angles. This is speculated to be due to the small amount of LiI added, which enters the material's lattice during dissolution and recrystallization, affecting the lattice spacing and potentially influencing the material's thermodynamic properties. Similar effects have been reported in other aluminum hydrides.

[0063] Figure 2 A scanning electron microscope image of a composite material g-C3N4 / LiAlH4 sample was obtained for this embodiment. In the absence of self-hydrogen release, the sample did not show widespread compaction, and the particle size was approximately 10 μm in agglomerates. At high magnification, the flaky morphology of g-C3N4 in the material could be observed, and micron-sized flower-like objects were formed by self-assembly. In addition, no obvious loaded particles were found in the material, and it is believed that LiAlH4 is attached to the g-C3N4 on the surface. Further determination of the particle size using transmission electron microscopy is required, but it is clear that the particle size of LiAlH4 is relatively small.

[0064] The morphology and particle size of the composite material were observed by spherical aberration corrected transmission electron microscopy images. Figure 3 As shown, Figure 3 (a) is the morphology of LiAlH4 nanoparticles under transmission electron microscopy. It is obvious that there are small particles coagulating at the edge of the particles. At a higher magnification, Figure 3 The size of the nanoparticles in (g) is clearly discernible, ranging from 10 to 20 nm. At high resolution, the lattice fringes of the material correspond to the (003) crystal plane of LiAlH₄. Notably, due to the material's sensitivity to radiation, the edges of the particles undergo a significant amorphization trend, and the actual particle size is smaller than that shown in the image. Diffraction rings of amorphous material are observed in the diffraction spot. Elemental distribution analysis indicates that the nanoparticles are formed by growth adhering to the g-C₃N₄ surface.

[0065] The hydrogen storage performance of the composite material samples was tested. Figure 4 It shows that before 150°C, the hydrogen release rate of the g-C3N4 / LiAlH4 sample is very slow, and the hydrogen release capacity is about 0.7wt%. However, when the temperature reaches about 150°C, the hydrogen release rate increases sharply, releasing about 5.4wt% of the gas within a few seconds. While the material is dehydrogenating, the material releases a large amount of heat, causing the temperature of the material in the reactor to rise suddenly from 150°C to about 170°C. The theoretical capacity of this material does not exceed 4wt%, but if the full hydrogen storage capacity of LiAlH4 (10.5wt%) is considered, it can match the actual hydrogen release capacity. However, in general, the dehydrogenation of LiH requires extremely high temperatures, about 650°C. Therefore, the actual hydrogen release path of the g-C3N4 / LiAlH4 sample needs further study, and it is expected that the anti-solvent loading has a great influence on the thermodynamic properties of the material.

[0066] In order to further understand the dehydrogenation kinetics of the composite material g-C3N4 / LiAlH4 sample prepared in this example, the kinetics of the two materials were explored by mass spectrometry coupled with programmed temperature rise. The materials were heated at heating rates of 3K / min, 5K / min, and 10K / min and the data were recorded. The point with the maximum dehydrogenation rate was found by mass spectrometry signal, and the activation energy of the reaction of the sample was calculated by the Kissinger equation. Figure 5 and 6 As shown in the mass spectrometry analysis of the g-C3N4 / LiAlH4 sample, two hydrogen desorption peaks were clearly distinguished. Activation energy fitting of each peak revealed that the activation energy for the first step was approximately 113.24 kJ / mol, and the activation energy for the second step was 104.223 kJ / mol. While the activation energy for the first step remained virtually unchanged compared to the original material, the activation energy for the second step was somewhat reduced. Therefore, the antisolvent method, with or without a catalyst, can significantly reduce the activation energy of the material, thereby improving its kinetic properties.

[0067] To further understand the changes in the g-C3N4 / LiAlH4 composite material sample produced in this example during the dehydrogenation process, differential scanning calorimetry (DSC) was used to examine the thermal evolution of the material from room temperature to 300°C. Mass spectrometry was also used to test the purity of the released gas to ensure that the assessment of the material's hydrogen storage capacity was not contaminated by other gases. The DSC test was performed in an aluminum crucible and argon was used as the inert carrier gas. Figure 7 Possible impurity gases are shown, including ammonia, methane and nitrogen. Mass spectrometry signals indicate that these impurity gases were not detected during the dehydrogenation process of the material. Figure 8 The DSC results in the study show a strong exothermic peak during the dehydrogenation process, a phenomenon previously unseen by the authors. This high DSC exothermic peak demonstrates that the antisolvent method combined with g-C3N4 nanosheets achieves thermodynamic modification of the material.

[0068] In order to better understand the phase changes of the composite material g-C3N4 / LiAlH4 sample prepared in this example during the entire hydrogen release process, the phase changes of the material during the heating process were explored by in-situ XRD. The test was carried out in a homemade XRD hydrogen storage in-situ tester. To prevent oxidation of the material during the transfer process, the sample was pressed into a glove box and sealed with Cape Town tape. Helium was continuously introduced into the glove box during the test to prevent interference of argon gas on X-ray absorption. Figure 9 As shown, within the initial temperature range of 30°C to 100°C, the LiAlH4 diffraction peak dominates the material, demonstrating its temperature stability within this range. Within the 100°C to 140°C range, the material begins to undergo a small amount of dehydrogenation, producing a certain amount of Li3AlH6. The Al diffraction peaks at 38° and 44° show a slight increase. At 143°C, the LiAlH4 peak remains, with a slight decrease in intensity compared to the initial state. At 146°C, the LiAlH4 peak disappears completely, while the Al peak increases in intensity, forming a gap compared to 143°C. From 143°C to 250°C, the Li3AlH6 initially produced gradually dehydrogenates and eventually disappears. Analysis of the dehydrogenation process reveals two main components: a large portion of the material exhibits rapid dehydrogenation at 143°C, driven by smaller particles, while another portion follows the dehydrogenation steps of the original LiAlH4. XRD results are consistent with the temperature-dependent dehydrogenation behavior, demonstrating rapid dehydrogenation within 3°C. Because the dehydrogenation of the material is a relatively fast process, the dehydrogenation is completed within the XRD scanning time range, so it is impossible to distinguish the phase change of the material during the dehydrogenation process.

[0069] The g-C3N4 / LiAlH4 composite material prepared in this example via an antisolvent method successfully achieved the loading of LiAlH4 nanoparticles (10-20 nm) onto g-C3N4, exhibiting dehydrogenation performance, releasing 5.4 wt% hydrogen within seconds at 150°C. The activation energy for the second-step dehydrogenation was reduced to 104.223 kJ / mol, demonstrating improved kinetic performance. XRD, TEM, and DSC analyses demonstrated that the antisolvent method combined with the g-C3N4 support optimized the material's structure and thermodynamic properties, providing an experimental basis for the study of solid-state hydrogen storage materials.

[0070] Example 2:

[0071] This embodiment provides a method for preparing a g-C3N4-loaded LiAlH4 composite material based on an anti-solvent method, comprising the following steps:

[0072] S1. Weigh LiAlH4 and anhydrous LiI and dissolve them in ether, stir thoroughly and filter with a syringe filter to remove insoluble matter to form a solution A, wherein the molar ratio of LiAlH4 to anhydrous LiI is 10:1;

[0073] S2. Weigh g-C3N4 and dissolve it in ether. Ultrasonicate for 0.5 hours to form solution B.

[0074] S3. Mix solution A and solution B and stir thoroughly to form solution C;

[0075] S4. Add n-pentane to a stainless steel cup at a ratio of 12:1. Use a semiconductor refrigerator to cool the n-pentane to -5°C.

[0076] S5. Insert the ultrasonic shear disperser 1-2 cm below the n-pentane liquid level, start ultrasonic shear dispersion, adjust the power so that the n-pentane liquid level does not fluctuate, and perform ultrasonic shear dispersion for 10 seconds and 10 seconds, for a total of 15 minutes;

[0077] S6. Pipette solution C and add it dropwise to n-pentane while ultrasound is on to form suspension D. Keep the semiconductor cooler on during this process.

[0078] S7. After the addition is completed, ultrasonic shear dispersion is continued for 8 minutes;

[0079] S8. Centrifuge the suspension D at 5000 rpm to obtain a precipitate;

[0080] S9. The precipitate was transferred to a tube furnace and dried in vacuum at 50 °C for 12 h to obtain a g-C3N4-loaded LiAlH4 composite material.

[0081] The mass ratio of the components of the composite material prepared in this embodiment is g-C3N4:LiAlH4=4:6, and the macroscopic morphology of the composite material is solid nanoparticles.

[0082] Example 3:

[0083] This embodiment provides a method for preparing a g-C3N4-loaded LiAlH4 composite material based on an anti-solvent method, comprising the following steps:

[0084] S1. Weigh LiAlH4 and anhydrous LiI and dissolve them in diethyl ether, stir thoroughly and filter with a syringe filter to remove insoluble matter to form a solution A, wherein the molar ratio of LiAlH4 to anhydrous LiI is 30:1;

[0085] S2. Weigh g-C3N4 and dissolve it in ether. Ultrasonicate for 2 hours to form solution B.

[0086] S3. Mix solution A and solution B and stir thoroughly to form solution C;

[0087] S4. Add n-pentane to the stainless steel cup at a ratio of 17:1. Use a semiconductor refrigerator to cool the n-pentane to -7°C.

[0088] S5. Insert the ultrasonic shear disperser 1-2 cm below the n-pentane liquid level, start ultrasonic shear dispersion, adjust the power so that the n-pentane liquid level does not fluctuate, and perform ultrasonic shear dispersion for 20 seconds and 20 seconds, for a total of 20 minutes;

[0089] S6. Pipette solution C and add it dropwise to n-pentane while ultrasound is on to form suspension D. Keep the semiconductor cooler on during this process.

[0090] S7. After the addition is completed, continue ultrasonic shear dispersion for 10 minutes;

[0091] S8. The suspension D was centrifuged at 6000 rpm to obtain a precipitate;

[0092] S9. The precipitate was transferred to a tube furnace and dried in vacuum at 40 °C for 12 h to obtain a g-C3N4-loaded LiAlH4 composite material.

[0093] The mass ratio of the components of the composite material prepared in this example is g-C3N4:LiAlH4=3:7, and the macroscopic morphology of the composite material is solid nanoparticles.

[0094] Example 4:

[0095] This embodiment provides a method for preparing a g-C3N4-loaded LiAlH4 composite material based on an anti-solvent method, comprising the following steps:

[0096] S1. Weigh LiAlH4 and anhydrous LiI and dissolve them in ether, stir thoroughly and filter with a syringe filter to remove insoluble matter to form a solution A, wherein the molar ratio of LiAlH4 to anhydrous LiI is 10:1;

[0097] S2. Weigh g-C3N4 and dissolve it in ether. Ultrasonicate for 0.5 hours to form solution B.

[0098] S3. Mix solution A and solution B and stir thoroughly to form solution C;

[0099] S4. Add n-pentane to the stainless steel cup at a ratio of 6:1. Use a semiconductor refrigerator to cool the n-pentane to -9°C.

[0100] S5. Insert the ultrasonic shear disperser 1-2 cm below the n-pentane liquid level, start ultrasonic shear dispersion, and adjust the power so that the n-pentane liquid level does not fluctuate. The ultrasonic shear dispersion program is 8 seconds of ultrasonication and 8 seconds of rest, for a total of 12 minutes;

[0101] S6. Pipette solution C and add it dropwise to n-pentane at a rate of 0.5 mL / min while ultrasound is on to form suspension D. Keep the semiconductor cooler on during this process.

[0102] S7. After the addition is completed, continue ultrasonic shear dispersion for 5 minutes;

[0103] S8. The suspension D was filtered to obtain a precipitate; filtration was performed using a microporous filter membrane having a pore size of 0.22-0.45 μm, under vacuum conditions of 0.01-0.08 MPa, and the filtration time was 5-15 minutes;

[0104] S9. The precipitate was transferred to a tube furnace and dried in vacuum at 30 °C for 12 h to obtain a g-C3N4-loaded LiAlH4 composite material.

[0105] The composite material prepared in this example is named g-C3N4 / LiAlH4, the mass ratio of the components is g-C3N4:LiAlH4=1:10, and the macroscopic morphology of the composite material is solid nanoparticles.

[0106] Example 5:

[0107] This embodiment provides a method for preparing a g-C3N4-loaded LiAlH4 composite material based on an anti-solvent method, comprising the following steps:

[0108] S1. Weigh LiAlH4 and anhydrous LiI and dissolve them in diethyl ether, stir thoroughly and filter with a syringe filter to remove insoluble matter to form a solution A, wherein the molar ratio of LiAlH4 to anhydrous LiI is 30:1;

[0109] S2. Weigh g-C3N4 and dissolve it in ether. Ultrasonicate for 3 hours to form solution B.

[0110] S3. Mix solution A and solution B and stir thoroughly to form solution C;

[0111] S4. Add n-pentane to the stainless steel cup at a ratio of 20:1. Use a semiconductor refrigerator to cool the n-pentane to -1°C.

[0112] S5. Insert the ultrasonic shear disperser 1-2 cm below the n-pentane liquid level, start ultrasonic shear dispersion, adjust the power so that the n-pentane liquid level does not fluctuate, and perform ultrasonic shear dispersion for 20 seconds and 20 seconds, for a total of 30 minutes;

[0113] S6. Pipette solution C and add it dropwise to n-pentane at a rate of 2 mL / min while ultrasound is on to form suspension D. Keep the semiconductor cooler on during this process.

[0114] S7. After the addition is completed, continue ultrasonic shear dispersion for 10 minutes;

[0115] S8. Centrifuge the suspension D at 10,000 rpm to obtain a precipitate;

[0116] S9. The precipitate was transferred to a tube furnace and dried in vacuum at 60 °C for 12 h to obtain a g-C3N4-loaded LiAlH4 composite material.

[0117] The composite material prepared in this example is named g-C3N4 / LiAlH4, the mass ratio of the components is g-C3N4:LiAlH4=5:5, and the macroscopic morphology of the composite material is solid nanoparticles.

[0118] The above examples are used to illustrate the present invention, which are only used to help understand the present invention and are not intended to limit the present invention. Those skilled in the art can make several simple deductions, modifications or substitutions based on the concept of the present invention.

Claims

1. A g-C3N4 loaded LiAlH4 composite material based on an anti-solvent method, characterized in that: The composite material is named g-C3N4 / LiAlH4, and the mass ratio of each component ranges from g-C3N4 to LiAlH4=1-5:5-10. The macroscopic morphology of the composite material is solid nanoparticles with a particle size of 10-20 nm.

2. The g-C3N4 loaded LiAlH4 composite material prepared by the anti-solvent method according to claim 1, characterized in that: The mass ratio of each component is g-C3N4:LiAlH4=5:

5.

3. The method for preparing the composite material according to claim 1 or 2, characterized in that: include: S1. Weigh LiAlH4 and anhydrous LiI and dissolve them in ether. Stir thoroughly and filter with a syringe filter to remove insoluble matter to form solution A. S2. Weigh g-C3N4 and dissolve it in ether, then sonicate to form solution B. S3, mixing solution A and solution B, and stirring thoroughly to form solution C; S4. Add n-pentane into the stainless steel cup, with the ratio of n-pentane to solution C being 6-20:1, and cool the n-pentane to -10-0°C using a semiconductor refrigerator; S5. Insert the ultrasonic shear disperser 1-2 cm below the n-pentane liquid surface, start ultrasonic shear dispersion, and adjust the power so that the n-pentane liquid surface does not fluctuate; S6. Use a pipette to draw up solution C, and add it dropwise to n-pentane while ultrasound is on to form suspension D. During this process, keep the semiconductor cooler on. S7, after the dropwise addition is completed, continue to perform ultrasonic shearing dispersion; S8. Centrifuge or filter the suspension D to obtain a precipitate; S9. The precipitate was transferred to a tube furnace and vacuum dried at 30-60°C for 12 hours to obtain a g-C3N4 loaded LiAlH4 composite material.

4. The method for preparing the composite material according to claim 3, characterized in that: In S1, the molar ratio of LiAlH4 to anhydrous LiI is 10-30:

1.

5. The method for preparing the composite material according to claim 3, characterized in that: In S2, the ultrasonic treatment time is 0.5-3 hours.

6. The method for preparing the composite material according to claim 3, characterized in that: In S5, the ultrasonic shearing dispersion procedure is ultrasonication for 5-20 seconds, and pause for 5-20 seconds, with a total duration of 10-30 minutes.

7. The method for preparing the composite material according to claim 3, characterized in that: In S6, the dropwise addition rate of solution C is 0.5-2 mL / min.

8. The method for preparing the composite material according to claim 3, characterized in that: In S7, the duration of the ultrasonic shearing dispersion is 5-10 minutes.

9. The method for preparing the composite material according to claim 3, characterized in that: In S8, the centrifugal speed is 5000-10000 rpm.

10. Use of the composite material according to any one of claims 1-2 or the composite material prepared by the preparation method according to any one of claims 3-9 in the field of solid-state hydrogen storage.

Citation Information

Patent Citations

  • N-rGO-coated NiCo catalyst loaded LiAlH4 composite material, preparation method and application

    CN118491553A